Benign Paroxysmal Positional Vertigo: Is It Really an Otolith Disease? - Koc, Ahmet (AVES, 2022)
The current theory in physiopathology of benign paroxysmal positional vertigo is the mechanical theory, namely the cupulolithiasis-canalolithiasis theory. Repositioning maneuvers based on this theory has now taken place in therapy. However, mechanical theory is insufficient to explain some clinical situations and cannot fully enlighten the physiopathology. Mechanical theory is based on very few histological studies. Currently, these few articles are still used for reference. Anatomically, there are uncertainties that need to be explained in this theory. In this literature review, the histological and anatomical evidence is reviewed and the value of mechanical theory in benign paroxysmal positional vertigo physiopathology has been questioned. Studies suggest that the debris in the semicircular canals is caused by degeneration due to aging and may not be responsible for the symptoms in benign paroxysmal positional vertigo. Some patients with debris in semicircular canals do not have benign paroxysmal positional vertigo symptomatology, while some patients without debris may have benign paroxysmal positional vertigo symptomatology. Experimental and histological findings suggest that vestibulopathy due to inflammation caused by neurotropic viruses may lead to benign paroxysmal positional vertigo picture. For all these reasons, in benign paroxysmal positional vertigo physiopathology, there must be other factors besides particle debris in semicircular canals.
Keywords: Benign paroxysmal positional vertigo; corticosteroid